2010
DOI: 10.5194/bg-7-1715-2010
|View full text |Cite
|
Sign up to set email alerts
|

Greenhouse gas fluxes in a drained peatland forest during spring frost-thaw event

Abstract: Abstract. Fluxes of greenhouse gases (GHG) carbon dioxide (CO 2 ), methane (CH 4 ) and nitrous oxide (N 2 O) were measured during a two month campaign at a drained peatland forest in Finland by the eddy covariance (EC) technique (CO 2 and N 2 O), and automatic and manual chambers (CO 2 , CH 4 and N 2 O). In addition, GHG concentrations and soil parameters (mineral nitrogen, temperature, moisture content) in the peat profile were measured. The aim of the measurement campaign was to quantify the GHG fluxes durin… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
32
0

Year Published

2011
2011
2017
2017

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 45 publications
(41 citation statements)
references
References 52 publications
4
32
0
Order By: Relevance
“…The concentrations of most of the measured elements were highest in the humus layer and lowest deeper in the peat (Table 1). The pH of the peat was 5.0 (Pihlatie et al, 2010). The concentration of soil NO − 3 was negligible, whereas the NH + 4 concentration in the peat varied between 5 and 15 mg N kg −1 and that of dissolved N between 75 and 225 mg N kg −1 soil (Pihlatie et al, 2010).…”
Section: Site Presentationmentioning
confidence: 99%
See 3 more Smart Citations
“…The concentrations of most of the measured elements were highest in the humus layer and lowest deeper in the peat (Table 1). The pH of the peat was 5.0 (Pihlatie et al, 2010). The concentration of soil NO − 3 was negligible, whereas the NH + 4 concentration in the peat varied between 5 and 15 mg N kg −1 and that of dissolved N between 75 and 225 mg N kg −1 soil (Pihlatie et al, 2010).…”
Section: Site Presentationmentioning
confidence: 99%
“…Direct measurements of the sub-canopy CO 2 fluxes have indicated that the ground layer of Kalevansuo was a C source in April-June (Pihlatie et al, 2010). However, this sub-canopy flux consists of not only the NEE of the peat and ground layer vegetation, but also the tree root respiration.…”
Section: Annual Uptake Of Co 2 Exceeds Peat Decompositionmentioning
confidence: 99%
See 2 more Smart Citations
“…Warm and dry conditions in peatlands can promote CO 2 uptake by enhancing GPP, diminish uptake by limiting moisture (Roulet et al, 2007;Charman et al, 2013) or accelerate CO 2 release by enhancing R (Hanson et al, 2000;Davidson and Janssens, 2006;Lund et al, 2010;Ise et al, 2008;Cai et al, 2010). In a dwarf-shrub pine bog, Pihlatie et al (2010) found that the CO 2 flux peak followed the increase in air and soil temperature closely, being higher (uptake) on warm and lower (emission) on cold days. They found an increase in the net uptake and emission of 4.3 and 2.5 g C m −2 d −1 , respectively, coincident with an average increase in air and soil temperature from 0 • C (late April) to 27 • C (early June).…”
Section: Introductionmentioning
confidence: 99%